The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1109/28.936398
|View full text |Cite
|
Sign up to set email alerts
|

Physical modeling and control of dynamic foaming in an LD-converter process

Abstract: Abstract-This paper deals with physical modelling and control of dynamic foaming in the LD-converter process. An experimental setup consisting of a water model, DSP and P C hardware is built up and showed to be useful for studying dynamic foaming. Furthermore, a foam height estimation algorithm is presented and validated through experiments. Finally, sound signals from the LD-converter and water model are compared and similarities between them are found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…Recently, for example, Buydens et al [10] published results from a technique including sound as well as vibration measurements for optimization and control of slag foaming in the EAF. In addition to the plant studies, several investigations on foaming behavior were carried out using physical modeling, as exemplified by the works of Komarov et al [11] and Birk et al [12].…”
mentioning
confidence: 99%
“…Recently, for example, Buydens et al [10] published results from a technique including sound as well as vibration measurements for optimization and control of slag foaming in the EAF. In addition to the plant studies, several investigations on foaming behavior were carried out using physical modeling, as exemplified by the works of Komarov et al [11] and Birk et al [12].…”
mentioning
confidence: 99%
“…Various methods for detecting slopping during blowing have been reported, including detection by a surveillance camera at the furnace mouth, [57][58][59] measuring furnace vibration with an accelerometer 60) and detection by acoustic signals. 61) M. Shakirov et al 62) reported the classification of slopping. Cicutti et al 63,64) conducted detailed research by an acoustic analysis during blowing.…”
Section: Sensing Techniques For Convertermentioning
confidence: 99%
“…Physical modeling of foaming is an arduous process as it requires estimation of foam height, which is dynamic in nature and differs for different bioprocesses . Machine learning based modeling helps mitigate the necessity for foam height estimation, and it can be generalized for any process, as it uses the available operational data for prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Physical modeling of foaming is an arduous process as it requires estimation of foam height, which is dynamic in nature and differs for different bioprocesses. 9 Machine learning based modeling helps mitigate the necessity for foam height estimation, and it can be generalized for any process, as it uses the available operational data for prediction. Recently, machine learning based methods have found several applications in sectors where mechanistic modeling is precluded by the inability to develop a model or generalize it for a process.…”
Section: Introductionmentioning
confidence: 99%